(untitled) (Journal of Forensic Medicine & Toxicology, 2026)
Stature estimation is one of the key techniques in forensic applications for personal identification in the context of miss ing person identification, disguised identification, and dead body identification when partial skeletal or body remains are available. The present study aims to explore the relationship between craniofacial measurement and stature. This study investigates these variances and formulates distinct equations for each sex. A sample of 44 males (age 28.5909±10.76) and 56 females (age 23.9286±8.34) from the Bengali-speaking population of West Bengal was selected using purpo sive sampling. Standard anthropometric techniques were employed to measure parameters such as Maximum Head Length (MHL), Maximum Head Breadth (MHB), Morphological Superior Facial Height (MSFH), Bigonial Breadth (BB), Auricular Length (AL), and Cephalic Index (CI). The parametric and non-parametric statistical tests were performed in SPSS version 23, including the Pearson correlation, independent t-test, ANOVA, and paired t-test. The result confirmed the marked sexual dimorphism, where all the anthropometric parameters are found significantly (p